Analisis Soal Tematik Bahasa Arab berbasis HOTS pada Kelas XII MAN 3 Jember - Kafi, Fina Aunul; Ilma, Zidni (UAS PRESS, 2022)
The failure of learning Arabic can occur because of the measurability of the tests used to test students' abilities which results in information on student learning outcomes that are not mapped properly. This article aimed to analyze the HOTS-based Arabic thematic test items for class XII MAN 3 Jember in the 2020/2021 academic year in ar-riyāḍah and ash-syabāb material. Researchers used quantitative methods with item measurement techniques through the multiple-choice item analysis application Anates Version 4.0.2. The research findings showed that of the 15 questions tested, there were 9 questions that had not been HOTS, reliability was 0.78, and distractors number 4, 10, 11, and 14 could not be used. There were 4 questions with inappropriate interpretation and the rest were feasible with improvement. The questions being tested still need to be corrected both qualitatively and quantitatively.